Effects of Injection Timing and Pilot Fuel on the Combustion of a Kerosene-diesel/Ammonia Dual Fuel Engine: A Numerical Study. (May 2017) - Tay, Kun Lin; Yang, Wenming; Chou, Siaw Kiang; Zhou, Dezhi; Li, Jing; Yu, Wenbin; Zhao, Feiyang; Mohan, Balaji
Abstract: It is well-known that the transportation sector consumes much petroleum as vehicles move goods and people around. From the many renewable and sustainable fuels proposed, ammonia is one such candidate. In this work, ammonia is introduced into a diesel engine via dual fuel mode whereby the fumigated premixed ammonia in the combustion chamber is ignited by a pilot fuel. The effects of injection timing and pilot fuel on the combustion of a kerosene-diesel/ammonia dual fuel engine are numerically investigated using the KIVA4-CHEMKIN code. It is interesting to note that as the injection timing is advanced, primary as well as secondary heat-release peaks are observed. The secondary heat-release peak is due to the combustion of residual fuel near the cylinder liner as well as in the crevice region and this is caused by an increase in in-cylinder temperature as injection timing advances. Also, as the pilot fuel is changed from diesel to kerosene, the primary peak heat-release increases with advancing injection timing.